Evolution of the Phenolic Content and Extractability Indices During Ripening of Nebbiolo Grapes from the Piedmont Growing Areas over Six Consecutive Years - Cagnasso, E.; Torchio, F.; Gerbi, V.; Río Segade, S.; Giacosa, S.; Rolle, L. (South African Journal of Enology and Viticulture, 2011)
The phenolic composition and extractability indices of grape berries play a key role in assessing red wine quality because the relationship between grape phenolic maturity and wine phenolic composition is well known. In this work, grape quality indices were determined in Nebbiolo grapes from two growing areas of Langhe (South Piedmont), at different stages throughout the ripening process in six consecutive years (2004 to 2009), with the aim of evaluating the ripening- and growing area-related changes in the grape indices separately. The effect of vintage was also investigated. Ripeness data were compared with analogous data determined in Nebbiolo grapes grown in the Carema area (North Piedmont). The vintage effect far outweighed any changes in the grape indices introduced by the ripening stage, even those arising from differences in the production area. In the Langhe and Carema zones, the average berry mass, pH, total acidity, total anthocyanins extractable at pH 3.2, total flavonoids and non-anthocyanin flavonoids extractable at pH 1, and the seed maturity index were seasonally dependent. The more ripening-affected parameters were the technological ones. This work highlights the importance of determining the phenol extractability, since it provides relevant information that allows improved management of the maceration stage.